De bootwerkersstaking. "Het lossen van een graanschuit door de patroons zelven, wegens gebrek aan volk". Uit: Wereldkroniek, 23-5-1896
De bootwerkersstaking. "Het lossen van een graanschuit door de patroons zelven, wegens gebrek aan volk". Uit: Wereldkroniek, 23-5-1896.